Vulneración de derechos en las cárceles de Colombia (2016)
This article seeks to establish the commitment of the Colombian state against people who are deprived of their liberty and to what extent they are violating the basic rights of inmates, how fair they are when applying justice in their favor even in prison and how proactive and intentional are being to achieve a process of resocialization once serve their sentences. The importance and need to intervene prisons of our country is urgent that these people can serve their sentences in decent conditions, areas of educational training and / or learning various arts, crafts or activities that lead is conducive to invest their spare time, which is much in occupations that certainly help improve their behavior, thus achieving impact positively and behavioral way the concept in prison not in order to be flexible, rather in order to be strong in Company building enforcing the law and relying on it, but as the time spent in these areas are carried out under decent conditions of human beings who eventually achieve meet the primary objective of the prison: resocialization